And So Life Goes - Barnes, Paul (Tufts Archival Research Center, 2006)
Paul Barnes relates a series of experiences in which he was helped by people of differing religious faith, socioeconomic status, political affiliations or skin color, and how these experiences affirm his belief in the essential goodness of people.